Delay Variation Model with RTP Flows Behavior in Accordance with M/D/1 Kendall's Notation - Miroslav Voznak; Michal Halas (Advances in Electrical and Electronic Engineering, 2010)
This paper focuses on the design of a mathematical model of end-to-end delay of a VoIP connection, in particular on a delay variation. It describes all partial delay components and mechanisms, its generation, facilities and its mathematical formulations. A new approach to the delay variation model is presented; its validation has been done by an experiment.